Capacidades organizacionais para escalabilidade em empresas digitais - Silva, Rosemeire de Souza Vieira (2025)
This thesis examines the relationship between financial organizational capabilities and the scalability of digital companies. The research adopts a quantitative approach, based on the analysis of secondary data obtained through the Crunchbase platform. The sample consists of 927 digital companies, whose data were extracted in April 2024. The analysis was conducted using multiple linear regression. The results confirm that investment attraction capability and acquisition capability are positively associated with scalability, reinforcing that access to capital and the strategy of company growth through acquisitions are central elements for digital companies to expand their operations and achieve scalability in a sustainable way. This research provides two empirical contributions. The first expands the Resource-Based View (RBV) to the digital context. Traditionally, the RBV explains how companies create competitive advantages through the management of their resources. The second contribution lies in the construction of a quantitative model to test financial organizational capabilities and understand their influence on the scalability of digital companies. Therefore, the findings highlight that organizational capabilities, especially the ability to attract investments and the ability to make acquisitions, play a fundamental role in the scalability of digital companies.